PELAKSANAAN MEDIASI SENGKETA INFORMASI PUBLIK DI KOMISI INFORMASI PROVINSI KALIMANTAN SELATAN - Tamliha Harun; Jumarianto Jumarianto (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2022)
The purpose of this study is to find out how the mechanism for implementing public information dispute mediation at the Information Commission of South Kalimantan Province, with the hope that public bodies as managers of public information and the public as users of public information know and understand the mechanism for resolving public information disputes through mediation at the Information Commission. This research uses descriptive-qualitative research, with interview, observation and documentation data collection techniques and then analyzed qualitatively. The research results can be described as follows; 1) The process of mediation activities at the Information Commission is an integral part of the process of non-litigation adjudication activities 2) Mediation activities are the first step in resolving public information disputes regarding open information caragories between the applicant and the respondent, guided by a mediator from the Information Commission Commissioner. 3) There are 3 (three) possible outcomes of mediation, namely successful mediation, failed mediation, and failed mediation. 4) If the mediation is successful (agreed), then the information dispute is considered completed. If mediation fails/fails, then the trial adjudication proceeds to the proof stage. 5) If the mediation is successful (agreed), then the results of the mediation are confirmed in the form of the Information Commission's Mediation Decision, and read out before the adjudication session. 6) The Information Commission mediation decision is legally binding on the parties, and must be implemented no later than 14 (fourteen) working days after the decision is read out.The purpose of this study is to find out how the mechanism for implementing public information dispute mediation at the Information Commission of South Kalimantan Province, with the hope that public bodies as managers of public information and the public as users of public information know and understand the mechanism for resolving public information disputes through mediation at the Information Commission. This research uses descriptive-qualitative research, with interview, observation and documentation data collection techniques and then analyzed qualitatively. The research results can be described as follows; 1) The process of mediation activities at the Information Commission is an integral part of the process of non-litigation adjudication activities 2) Mediation activities are the first step in resolving public information disputes regarding open information caragories between the applicant and the respondent, guided by a mediator from the Information Commission Commissioner. 3) There are 3 (three) possible outcomes of mediation, namely successful mediation, failed mediation, and failed mediation. 4) If the mediation is successful (agreed), then the information dispute is considered completed. If mediation fails/fails, then the trial adjudication proceeds to the proof stage. 5) If the mediation is successful (agreed), then the results of the mediation are confirmed in the form of the Information Commission's Mediation Decision, and read out before the adjudication session. 6) The Information Commission mediation decision is legally binding on the parties, and must be implemented no later than 14 (fourteen) working days after the decision is read out.